Effect of acupressure therapy point HT 6 and LI 4 on post cesarean sectio’s pain - Nani, Desiyani; Maryati, Susio; Rahmaharyanti, Rizka (International Journal of Research in Medical Sciences, 2017)
Background: Stimulation at acupressure point can activate three centre of body control, there are spinal cord, midbrain, and pituitary to release neurochemical such as endorphin, serotonin, and norepinephrine effect to blockage pain. Cesarean sectio’s pain begins since decreasing of the effect from anesthetical medication. Acupressure therapy at point HT6 and LI4 can activate these three centre of body control. So it is possible to reduce pain sensation when stimulated both. This study was carried out to identify the effects of HT 6 and LI 4 acupressure on sectio cesarea’s pain in post-partum periods. Methods: A single blind randomized clinical trial is performed on seven eligible women who are at the beginning of post-partum periods. The participants are matched duration after sectio cesarean before 24 hours, nulliparas and multiparas. There is no additional administration of analgesics during the study period. The women receive acupressure at HT 6 and LI 4 for 20 minutes. The severity of pain is measured by using the Visual Analogue Scale for pain. Intensity of pain are measured before and immediately after the intervention. Statistical analyses are perform using SPSS 20. Results: the rate of pain intensity’s scale before and after treatment are ( 84,29 ± 15,65) and (64,57 ± 15,80). There are significant differences between both of groups. The pain intensity after the intervention was significantly decrease than pain intensity before (p = 0.04). There are significant differences between the groups in subjective pain scale before intervention and immediately after intervention. The pain intensities after the intervention are significantly decrease than pain intensities before the intervention (p = 0.04). Conclusions: Acupressure at HT6 and LI4 point reduced the severity of pain at the beginning of post partum periods after cesarean sectio. These findings show that combination HT6 and LI4 acupressure are effective for reducing esarean sectio’s pain. HT6 and LI4 acupressure can be an effective nursing management for women in post partum periods.